Agricultural bio-waste materials as potential sustainable precursors used for activated carbon production: A review - Yahya, MA; Al-Qodah, Z; Ngah, CWZ (Pergamon-Elsevier Science Ltd, 2024)
A review on the preparation of the activated carbon from agricultural waste material is presented. The physical properties such as proximate and ultimate analysis of agricultural waste material were reviewed. The chemical compositions such as cellulose, hemicelluloses and lignin contents were also discussed. The effects of various parameters on the preparation such as carbonization and activation temperature, time, types of activating agents and impregnation ratio were reviewed. Various physical and chemical processes for the activation of the agricultural residues and their effects on the textural properties such as surface area and pore volume were discussed. The low cost, renewable and relatively less expensive of the agricultural waste were found to be efficiently being converted into wealth. The uses of activated carbon derived from agricultural residues in many fields were evidently proven in the review. The reaction kinetic modeling on the pyrolysis and activation of agricultural wastes were also reviewed. (C) 2015 Elsevier Ltd. All rights reserved.